EVALUATION OF THE PROTEIN QUALITY OF BEANS, CORN, AND WHEAT GRAINS INFESTED BY INSECT PESTS - MENDES, FABRÍCIA QUEIROZ; OLIVEIRA, MARIA GORETI DE ALMEIDA; COSTA, NEUZA MARIA BRUNORO; PASSOS, FLÁVIA REGINA; ROSA, JOSÉ CÉSAR; GUEDES, RAUL NARCISO CARVALHO; DE OLIVEIRA, JOEL ANTÔNIO (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2017)
Insect infestation of grains causes several types of damage, including reduced grain weight, heat damage and consequent deterioration, diminished market value, and decreased nutritional value due to grain consumption by insects. The goal of this study was to compare the digestibility, chemical score, protein digestibility corrected amino acid score (PDCAAS), protein efficiency ratio (PER), and net protein ratio (NPR) of infested and uninfested grain flours. This study found that infested grain flours had higher nitrogen contents than uninfested grain flours. The presence of insects did not alter the digestibility of the analyzed grains. However, insects decreased the PER and NPR for beans but not corn and wheat. Similarly, there was a greater reduction in the levels of essential amino acids for beans than for corn and wheat. Insect infestation reduces the nutritional quality of grains, although the type of insect and the grain quality determine the extent of this reduction